Surgical Strategies to Improve Fixation in the Osteoporotic Spine: the Effects of Tapping, Cement Augmentation, and Screw Trajectory. (February 2014) - Kuhns, Craig A.; Reiter, Michael; Pfeiffer, Ferris; Choma, Theodore J.
Study Design: Biomechanical study of pedicle screw fixation in osteoporotic bone. Objective: To investigate whether it is better to tap or not tap osteoporotic bone prior to placing a cement-augmented pedicle screw. Methods: Initially, we evaluated load to failure of screws placed in cancellous bone blocks with or without prior tapping as well as after varying the depths of tapping prior to screw insertion. Then we evaluated load to failure of screws placed in bone block models with a straight-ahead screw trajectory as well as with screws having a 23-degree cephalad trajectory (toward the end plate). These techniques were tested with nonaugmented (NA) screws as well as with bioactive cement (BioC) augmentation prior to screw insertion. Results: In the NA group, pretapping decreased fixation strength in a dose-dependent fashion. In the BioC group, the tapped screws had significantly greater loads to failure ( p < 0.01). Comparing only the screw orientation, the screws oriented at 23 degrees cephalad had a significantly higher failure force than their respective counterparts at 0 degrees ( p < 0.01). Conclusions: Standard pedicle screw fixation is often inadequate in the osteoporotic spine, but this study suggests tapping prior to cement augmentation will substantially improve fixation when compared with not tapping. Angulating screws more cephalad also seems to enhance aging spine fixation.